INTERDISCIPLINARY CHARACTER OF COGNITIVE STYLISTICS. - Rakhimova Gulchekhra Obidjonovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This study explores the interdisciplinary character of cognitive stylistics, emphasizing its deep integration with various cognitive sciences. Cognitive stylistics, a subfield of cognitive linguistics, draws upon multiple disciplines including psychology, neuroscience, computer science, linguaculturology, and pragmatics to analyze how readers comprehend, interpret, and derive meaning from literary texts. The paper highlights the principles of cognitive psychology, such as perception, memory, and schema theory, as foundational to understanding the cognitive processes involved in reading. It also discusses the contributions of neuroscience to the empirical validation of stylistic theories, and the role of computer linguistics in offering quantitative tools for text analysis. The interdisciplinary nature of cognitive stylistics not only enhances its theoretical depth but also aligns it with the anthropocentric paradigm prevailing across modern linguistics and cognitive sciences.